Strengthening Medical Record Management Through Training, Monitoring, Tracer Implementation, and Standard Operating Procedures to Reduce Delays in Outpatient Medical Record Returns - Wijianto, Ahdan Setyo; Alfiansyah, Gamasiano; Rachmawati, Ervina; Rahargiyanto, Angga (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Timely return of outpatient medical records is an important component of effective health information management in primary healthcare facilities. Proper management of medical records ensures the continuity of patient care and supports administrative and reporting functions. This study aimed to analyze the factors causing delays in the return of outpatient medical records at Community Health Center (Puskesmas) X based on predisposing, enabling, and reinforcing factors. This study employed a qualitative research design involving nine participants, consisting of one operational coordinator of the medical record unit, one medical record officer, and seven polyclinic staff members. Data were collected through in-depth interviews, observations, documentation review, and brainstorming sessions. The data were then analyzed to identify key factors contributing to delayed medical record returns. The results revealed several contributing factors to the delay. Predisposing factors included the presence of medical record staff who did not meet the minimum educational qualification of a diploma in medical record management and limited compliance among nursing staff regarding the required return time. Enabling factors involved the suboptimal use of expedition logbooks and the absence of tracer tools in the medical record borrowing process. Reinforcing factors included the lack of standard operating procedures (SOPs) regulating the return of medical records. Several improvement strategies were identified, including proposing medical record management training, assigning monitoring responsibilities to polyclinic coordinators, developing and implementing tracer systems, applying administrative sanctions such as additional tasks or point-based accountability mechanisms, and establishing formal SOPs for medical record return procedures. In conclusion, strengthening staff capacity, monitoring mechanisms, record tracking systems, and institutional regulations is essential to improve compliance with medical record return timelines and reduce delays in outpatient medical record management.Keywords: delay; medical records; primary healthcare center; health information management; outpatient services